Effects of anisotropy and pre-strain on the shear fatigue behaviour of DP600 steel. Issue 14 (22nd September 2022) - Zhang, Zhongran; Yue, Zhenming; Bao, Yanmei; Gao, Jun
Abstract : The effects of anisotropy and pre-strain on the low-cycle-fatigue properties of DP600 steel sheet under shear path were investigated. Fully reversed strain-controlled fatigue tests were performed along the 0° and 90° directions with the initial strain direction. The cyclic-loading amplitude determined whether the pre-strained material had a hardening process. The high dislocation density in the crystals of pre-strained material can promote the formation of low-energy substructures, obviously accelerating the cyclic-softening rate and reducing the fatigue life. Average plastic strain energy density was affected by the pre-straining state and loading direction and had a linear relationship with the strain amplitude. Overall, these results can be used to verify the calculation model of structural parts.